A Method of Building Ontology Based Information knowledgebase - Kaity, S; Das Gupta, PK; Jana, B (International Journal of Computer Sciences and Engineering, 2025)
The knowledge about missile we want to make is represented in ontology. In philosophy, an ontology is “a particular theory about the nature of being or the kinds of existents”. It also covers the basic question on how to record the real world. Tom R Gruber discuss a more technical view of ontology, the most prominent definition being “An ontology is an explicit specification of a conceptualization”. This definition is often extended by three additional conditions: “Ontology is an explicit, formal specification of a shared conceptualization of a domain of interest”. The reference to a domain of interest indicates that for domain ontology one is not interested in modeling the whole world, but rather in modeling just the parts which are relevant to the task at hand. Ontology of missile can be used for proper classification of articles and it helps for information extraction and answering to a search query. Ontology knowledge base for missile is generated using OWL ontology language and it helps to extract information and answering to user queries. This ontology is capable of answering any missile related queries of user interest and it knowledgebase can be enriched by populating new information related to missile. This ontology can help to prioritise multi sensor tracking systems for better tracking coverage and accuracy.